Research on the impact of digital finance on regional innovation - Cheng, Zhizhe (Transactions on Economics, Business and Management Research, 2024)
Innovation is indispensable for the high-quality self-reliance and development of an economy and society in a country.At present, Chinas existing innovation capacity is still unable to meet the needs of economic development.This paper focuses on how digital finance affects regional innovation in China.The findings show that digital finance has a significant positive promotion effect on regional innovation, and this promotion effect has been gradually strengthening over time.